Sleep profile of elderly patients undergoing hemodialysis - Allemand,Ludimila D'Avila e Silva (2017)
INTRODUCTION: Sleep disturbances are frequently observed in the elderly population. The objective of this study was to evaluate, by means of qualitative and parametric analyses, the sleep pattern of elderly people undergoing dialysis. METHODS: This crosssectional study was performed at three hemodialysis centers, with a convenience sample composed of 28 patients who fulfilled the inclusion criteria. Their sleep quality was analyzed by means of the Pittsburgh index and actimetric measurements for seven days with the following variables: total nocturnal sleep time (TNST), time awake after the onset of sleep (TAOS), number of nocturnal awakenings (awakenings), total daytime sleep time (TDST), number of naps, and percentage of nocturnal sleep (% sleep). RESULTS: Seventeen patients (58.6%) presented PSQI > 5, characterizing poor quality sleep in the last 30 days. The actimetric analyses demonstrated poor parameters on average: TNST of 341. 2 ± 90.8 minutes per night; TAOS of 91.1 ± 46.44 minutes per night, % sleep of 79.6 ± 9.8 per night; 28.5 ± 11.4 times woken up per night; 48.5 ± 14.6 naps per day, and TDST of 222.4 ± 73.9 minutes per day. CONCLUSION: This study observed, by means of a subjective qualitative analysis (PSQI) and actimetric parameters (actimetry), that elderly people undergoing hemodialysis demonstrate having poor sleep quality.